On Minimally Nonouterplanarity of the Semi Total (Point) Graph of a Graph (Journal of Scientific Research, 2009)
We present here characterizations of graphs whose semi total (point) graphs are outerplanar and k-minimally nonouterplanar (k = 1, 2 or 3).Keywords: Semi total (Point) graph; Minimally nonouterplanarity; Outerplanar; Block.© 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.DOI: 10.3329/jsr.v1i3.2578      J. Sci. Res. 1 (3), 551-557 (2009)